Optimization strategies for ultrasound zoning of cervical lymph nodes in esophageal cancer: a precision medicine approach - Zhu, Yi; Fan, Yuting; Luo, Xinyi; Chen, Hainan; Liang, Shuoming; Xiong, Jicheng; Daiko, Hiroyuki; Leng, Xuefeng (Frontiers in Oncology, 2025)
Esophageal cancer is a common malignancy with high incidence and mortality rates. Its pathological types vary by region, with squamous cell carcinoma predominant in Asia and adenocarcinoma in Western countries. Accurate staging before treatment is crucial for selecting appropriate therapeutic strategies. The existing international staging systems primarily include the American Joint Committee on Cancer and Union for International Cancer Control (AJCC/UICC) system and the Japanese Esophageal Society (JES) system. However, these systems differ in lymph node definitions and zoning, particularly regarding the classification and management of supraclavicular lymph nodes, which remains a contentious issue. Accurate zoning of the supraclavicular and cervical lymph nodes directly impacts treatment decisions for esophageal cancer, making precise ultrasound-based zoning diagnosis essential. Currently, the cervical lymph node zoning for esophageal cancer often follows the ultrasound standards established by the American Head and Neck Society and the American Academy of Otolaryngology-Head and Neck Surgery (ASHNS/AAO-HNS). However, the applicability of these standards to esophageal cancer is still under debate. Notably, the challenges associated with cervical lymph node zoning in esophageal cancer are particularly prominent in East Asia, especially in China and Japan, where squamous cell carcinoma is the predominant histological type and the JES staging system is widely adopted. In this system, supraclavicular lymph nodes are considered surgically resectable regional nodes, and their dissection is recommended as it may offer survival benefits. In contrast, clinical practice in Western countries primarily follows the AJCC/UICC staging system, which classifies supraclavicular lymph nodes as distant metastases (M1), generally precluding surgical intervention. These geographical and conceptual discrepancies in staging and treatment strategies highlight the urgent need to establish a globally applicable and standardized ultrasound-based lymph node zoning approach. This article aims to explore the optimization of ultrasound zoning for cervical lymph nodes in esophageal cancer based on literature and clinical practice, providing insights for precise staging and optimal treatment.